(untitled) - Gorge Heard Hamilton (New York, 1983)
The book traces the origins and growth of modern art, assessing the intrinsic qualities of individual works and describing the social forces in play. The results is an authoritative guide through the forest of artistic labels - Impressionism and Expressionism, Symbolism, Cubism, Constructivism, Surrealism, etc. - and to the achievements of Degas and Cézanne, Ensor and Munch, Matisse and Kandinsky, Picasso, Braque and Epstein, Mondrian, Dali, Modigliani, Utrillo and Chagall, Klee, Henry Moore and many other artists in a revolutionary age
Keywords: painting, modern - 19th century - history,painting, modern - 20th century - history